Fetal right aortic arch: associated anomalies, genetic anomalies with chromosomal microarray analysis, and postnatal outcome. (22nd March 2017) - Peng, Ruan; Xie, Hong‐Ning; Zheng, Ju; Zhou, Yi; Lin, Mei‐Fang
Abstract: Objectives: The aim of the study was to assess the associated prenatal findings, genetic anomalies with chromosomal microarray analysis (CMA) and postnatal outcome of fetal right aortic arch (RAA). Methods: This retrospective study reviewed 92 fetuses diagnosed with RAA and the findings of CMA using Affymetrix CytoScan HD array in our institution between 2013 and 2016. Results: Postnatal data were not available for six cases, and genetic data were not available for 26 cases. Tetralogy of the Fallot was the most frequently associated anomaly. Among the 60 fetuses with known karyotype, one was 46, X, Yqh+, der(13)t(8;13)(q22.3;q33.2), one was 47, XYY and the remaining were normal. Our study showed that CMA could detect uncertain significant copy number variants in 5.2% of fetal RAA and pathogenic copy number variants in 5.2%, all of which were microdeletion in chromosome 22q11.21. The genetic anomalies, gestational age at delivery and postnatal death were not significantly different between RAA‐no intracardiac anomalies and RAA‐intracardiac anomalies group. One infant with aberrant left subclavian artery needed to perform a surgery for respiratory symptom. Conclusions: A right aortic arch is associated with 22q11.2 deletion syndrome in approximately 5% of cases, and, therefore, prenatal testing, preferably using CMA, should be offered. © 2017 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Fetuses with RAA carried a risk of genetic anomalies, including 22q11.2 deletion syndrome. CMA could lead to an incremental detection of causal chromosomal imbalances in fetuses with CHDs. What does this study add? Our study showed that pathogenic CNVs in 5.2% of prenatally diagnosed RAA, all of which were microdeletion in chromosome 22q11.21. In addition to 22q11.2 deletion syndrome, approximately 5.2% have copy number variants of unknown clinical significance at the present time.